PENGARUH BRAND IMAGE DAN WORD OF MOUTH TERHADAP LOYALITAS KONSUMEN PADA KAFE HITAM PUTIH PADANG BULAN MEDAN - Tambunan, Formaida; Siregar, Marupa; Telaumbanua , Firman (JURNAL MUTIARA MANAJEMEN, 2024)
In today's business world, cafes are one of the most popular businesses in society. So in this case, several steps are needed to strengthen the business sector owned. This study discusses the factors that can increase consumer loyalty, namely brand image and word of mouth. The purpose of this study is to determine the effect of brand image and word of mouth on consumer loyalty both partially and simultaneously. The method used in the study is quantitative with an associative approach. Data collection techniques using questionnaires. The analysis method used is multiple linear regression analysis. The population in this study was 4,500 people, and the sample in this study was 98 respondents obtained using the Slovin formula. The results of the study indicate that brand image (X1) and word of mouth (X2) partially (t-test) have a positive and significant effect on consumer loyalty. Based on the simultaneous test (F), the results show that brand image and word of mouth have a positive and significant effect on consumer loyalty. Based on the results of the determination coefficient test (R2), it shows that brand image and word of mouth are able to influence consumer loyalty by 83.6%.